Awareness and attitudes towards emergency contraceptive pills among young people in the entertainment places, Vientiane City, Lao PDR - Sychareun, Vanphanom (BioMed Central, 2013)
BACKGROUND: Emergency Contraception is not officially available to the public sector in Laos. The potential of emergency contraception to prevent unwanted pregnancies is well documented in developed countries, but in Laos no studies of ECPs exist. This study aimed to assess knowledge of and attitudes towards emergency contraceptive pills (ECPs) in Vientiane, the capital city of the Lao PDR. METHODS: A cross-sectional survey was conducted among 500 young adults in entertainment venues by using the convenience sampling between May to July, 2007. Data were obtained through face-to-face interview. Participants were asked about socio- demographic characteristics, knowledge, attitudes related to ECPs, and source of information about ECPs. Data analysis was performed with chi-square test and logistic regression (p < .05). RESULTS: Only 22.4 percent of respondents had heard of ECPs and of these only 17.9 percent knew the correct time-frame for effective use. Most of the respondents (85%) agreed on the need for ECPs to be available in Laos and 66.8 percent stated that they would use them should the need arise, if they were available. Among those who said they would not use ECPs, 63.8 percent were concerned about possible health effects, or other side effects. Awareness of ECPs was associated with increasing age (OR = 2.78, p = .025) and male sex (OR = 2.91, p = .010). CONCLUSIONS: There is needed to provide effective health education about the method, timing of use, and how to obtain ECPs through both informal, peer channels, and also through formal channels such as health care providers.